Effect of Proprioceptive Training and Strength Training on Agility amongTable Tennis Players - Barathsha, Basha; Suryaprakash, Nagaraj; Hari Hara, Sudan; Manoj, Abraham (INTI International University, 2023)
Background: Table tennis is a dynamic sport. Proprioception is an important sensory and motor function for all mobility action which also plays an important role in sports and contribute greatlyto the performance of athletes. Strength training involves the performance of physical exercise thatare designed to improve strength. Agility is the ability to move and change the direction and position of the body quickly and effectively under control. Objective: To find out effect of proprioceptive training and strength training on agility among table tennis players. Methodology: The study design was experimental study, conducted in KG college of Physiotherapy with total sample of 20 players were included in the study with 10 players each in the group. Sampling method was convenient sampling. Study duration was 6 months and individual training was 6 weeks. Male table tennis players, aged between 18-25 years who were practicing and playing table tennis for more than one year were included in the study. Players withany soft tissue injuries, recent fractures, recent musculoskeletal surgeries and neurological problems, irregular in training regime have been excluded. Result: The post-test mean values of proprioceptive training group (N=10) was 9.38 whereas the players who are underwent strength training (N=10) was 10.20. Thus, proprioceptive training reflects better agility when compared with the strength training. Conclusion: Agility involves starting, stopping, changing the direction, rotation, reaction and complex movements. Table tennis realize heavily on agility. Thus, proprioceptive training and strength training has to been given for better agility among table tennis players who are underwent proprioceptive training showed significant improvement in agility than strength training.